Pengaruh Biaya Produksi terhadap Pendapatan Pengrajin Tenun di Desa Sukarara Kecamatan Jonggat Kabupaten Lombok Tengah - Ely Susilawati; Yohana Yohana; Refreandi Haeri (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study aims to analyze the effect of production costs on the income of weaving artisans in Sukarara Village, Jonggat District, Central Lombok Regency. The research employed a quantitative approach with an explanatory design. The population consisted of all weaving artisans in Sukarara Village, with a sample of 30 respondents selected through purposive sampling. The primary instrument was a questionnaire, while the data were analyzed using simple linear regression, t-test, and the coefficient of determination (R²). The results reveal that production costs have a positive and significant effect on artisan income. The t-test yielded a calculated t-value of 3.620 with a significance level of 0.001 (<0.05), supporting the acceptance of the alternative hypothesis. The coefficient of determination (R²) of 0.319 indicates that 31.9% of the variation in artisan income is explained by production costs, while the remainder is influenced by other factors. These findings emphasize the importance of efficient cost management to improve income. Local government support in the form of business management training and expanded market access is strongly recommended